Fiscal weakness, the (under-) provision of public services, and institutional reform (2020)
The fact that many developing countries spend little on growth-promoting public services is often blamed on “fiscal weakness”. We propose a novel framework to study the consequences of an exogenous improvement in public revenues. We demonstrate that higher revenues may induce the group in power to use a dual repression approach, one pillar of which is to aggravate the “underspending” on growth-promoting public services. However, we also identify circumstances in which the group in power will abstain from repression and instead opt for institutional reform. This result contrasts with the view that exogenous revenue improvements necessarily undercut growth-promoting institutions. JEL classification: D70; O11; F53; H50; Q34. © The Author(s) 2020.